Ecologically Friendly Sourcing in Developing Countries: A Non-Food Case Study - Sander de Leeuw; Wout Dullaert; Abderrahim Ouaderzan (Logistics)
The purpose of this paper is to investigate how nearby sourcing versus long-distance sourcing affects the ecological friendliness—operationalized in terms of energy efficiency—of a supply chain for a non-food item in a developing country. Using case research, we show that the average energy needed to supply a pair of imported shoes to a retailer in Morocco is less than the average energy needed to supply a pair of locally produced shoes. These findings highlight the need to assess the true total energy effects of nearby sourcing versus long-distance sourcing since the outcomes of such assessments may be more complicated than they appear upon first glance, particularly in developing countries.